AS AVENTURAS DO MARXISMO NO BRASIL - Musse, Ricardo (Caderno CRH, 2015)
<!DOCTYPE html PUBLIC "-//W3C//DTD HTML 4.01 Transitional//EN"> 74 musse A meditação acerca da importância e dolugar domarxismo na sociedade brasileira – seja na vidapolítica esocial, seja na produção intelectual e cultural–adquiriu uma via privilegiada com a conclusão da obracoletivaHistória do marxismo no Brasil. Um inventário,mesmo queprecário, de suas lacunas esuperposiçõestambém abre espaço para um balanço daprodução bibliográfica sobre omarxismobrasileiro. A partir disso, torna-se possível destacarestruturas e tendências em seu desenvolvimentohistórico. Palavras-chave: Marxismo brasileiro. Partido Comunista do Brasil (PCB).Partido dos Trabalhadores (PT). História do marxismo noBrasil. THEADVENTURES OF MARXISM IN BRAZIL Ricardo Musse The thinking on the importance and the place of Marxism in Braziliansociety, be it in political and social life, be it in the intellectualand cultural output, has gained an outstanding path with the completionof the collective work History of Marxism in Brazil. An inventory, evena precarious one, of its gaps and overlaps also allows for an overviewof the bibliographic output on Brazilian Marxism. Starting from this,it becomes possible to highlight structures and trends in itshistorical development. Keywords: Brazilian Marxism. Communist Party of Brazil.Workers’Party (Brazil). History of Marxism in Brazil. LESAVENTURES DU MARXISME AUBRÉSIL Ricardo Musse La réflexion concernant l’importance et la placedumarxisme dans la société brésilienne– quece soit dans la vie politique et sociale ou dans la productionintellectuelle et culturelle – a acquis une placeprivilégiée grâce à laconclusion del’ouvrage collectif Histoire du marxisme auBrésil. Uninventaire de ses lacunes et de ses chevauchements qui, mêmes’il reste précaire, permet de faire un bilan delaproduction bibliographique sur le marxismebrésilien. Ilest alors possible de mettre en évidence les structures etlestendances de son développement historique. Mots-clés: Marxisme brésilien. Parti CommunisteduBrésil (PCB). Parti des Travailleurs (PT). Histoire dumarxismeau Brésil. <small style="color: rgb(0, 0, 0); font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; background-color: rgb(255, 255, 255);">PublicaçãoOnlinedo Caderno CRH no Scielo: http://www.scielo.br/ccrh<span style="color: rgb(0, 0, 0); font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; font-size: 12px; float: none; display: inline ! important; background-color: rgb(255, 255, 255);"> <br style="color: rgb(0, 0, 0); font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; font-size: 12px; background-color: rgb(255, 255, 255);"><br style="color: rgb(0, 0, 0); font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; font-size: 12px; background-color: rgb(255, 255, 255);"><small style="color: rgb(0, 0, 0); font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; background-color: rgb(255, 255, 255);">PublicaçãoOnlinedo Caderno CRH: http://www.cadernocrh.ufba.br<span style="color: rgb(0, 0, 0); font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; font-size: 12px; float: none; display: inline ! important; background-color: rgb(255, 255, 255);">